Work–Family Conflict, Job Stress, and Burnout as Predictors of Turnover Intention: Evidence from Central Java - Andini, Audina Citra; Muhdiyanto, Muhdiyanto; Ibrahim, Muhammad Wahid (Borobudur Management Review, 2025)
Turnover intention is something that is really taken into account by companies. The KSPPS BMT Tumang in Central Java shows a fluctuating level of turnover intention. This research aims to examine the influence of multiple role conflict, work stress, and burnout on turnover intention. The population in this study were all KSPPS BMT Tumang employees in Central Java. The sampling method in this research used purposive sampling with a total sample of 107 respondents. The sample criteria in this study are female employees who are married and the employee has worked for at least 2 years. The analytical tool used in this research is multiple linear regression. The results of this study show that dual role conflict has no effect on turnover intention, work stress has a positive effect on turnover intention, while burnout has no effect on turnover intention.